Double-Illumination All-Optical Nanoalignment for Stacking X-Ray Fresnel Zone Plates - Siqi Wang; Cheng Jiang; Robert Peters; Mirwais Aktary; Jinyang Liang (Advanced Devices & Instrumentation)
Fresnel zone plate (FZP) stacking is an approach to enhance diffraction efficiency in x-ray focusing and imaging by physically aligning 2 or more FZPs to increase the effective thickness and optical efficiency. Existing methods face limitations in x-ray-source availability, controlled degrees of freedom, alignment accuracy, and contact-induced friction. To overcome these limitations, we develop a double-illumination all-optical nanoalignment (DIANA) system. Designed to leverage the x-ray FZP chip’s nanopatterned characteristics, DIANA uses coherent illumination in reflection mode to implement laser interferometry for accurate tilt and yaw adjustment. It also employs incoherent illumination in transmission mode for high-contrast nanoalignment using Vernier/main scales and moiré fringes. Using DIANA, we demonstrate the stacking of 2 x-ray FZPs with under 30-nm alignment accuracy.